ANALISIS FIQH TERHADAP PENETAPAN MARGIN KEUNTUNGAN DALAM AKAD MURABAHAH - Abdurrahman Putera Nugroho; Gama Gama; Muhammad Fattir Aufa Azzir; Muhammad Dzaki Al Faruq (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study analyzes the concept of profit margin determination in murabahah contracts from the perspective of fiqh muamalah. Murabahah, as a widely used financing instrument in Islamic financial institutions, often encounters controversy due to the practice of setting margins based on conventional interest benchmarks such as the BI Rate. This raises concerns about its compliance with sharia principles. Using a qualitative approach through literature review, the study examines classical and contemporary fiqh views, regulatory fatwas, and empirical findings on margin determination practices. The results show that while murabahah is legally valid under Islamic law, the current implementation in many institutions deviates from its original intent, particularly regarding transparency, fairness, and independence from riba-based benchmarks. The study recommends a cost-plus pricing model that incorporates real operational costs, transaction risk, and maqashid al-shari’ah considerations. It also emphasizes the need to enhance the role of Sharia Supervisory Boards and issue regulatory guidelines to ensure margin setting aligns with Islamic ethical standards. This research contributes to the discourse on aligning modern Islamic financial practices with the foundational values of justice, transparency, and public interest in Islamic economics.Keywords: fiqh muamalah, Islamic finance, margin, murabahah, sharia compliance